The effects of competitive and interactive play on physiological state in professional esports players - Watanabe, K.; Saijo, N.; Minami, S.; Kashino, M. (Heliyon, 2021)
In esports competitions, both motor skills used to manipulate an avatar and psychological skills are important to achieve optimal performance. Previous studies have investigated the role of psychological skill on computer game performance by observing the modulation of physiological state. However, how physiological state is modulated in esports athletes during an esports match is unclear. In this study, we examined two hypotheses to clarify the effects of competitive and interactive play on the physiological state of esports professionals: (1) the sympathetic nervous system of esports players is activated by competitive play and modulated by the game situation, and (2) the autonomic nervous system activities of players in dyads are synchronized positively/negatively by interpersonal interaction. We measured electrocardiograms (ECGs) in nine professional esports players while they played a fighting video game to investigate changes in physiological state. We compared ECGs collected in the resting state, while playing against a computer, and while playing against other players. We calculated the mean heart rate (HR), temporal pattern of HR, and correlation of temporal HR patterns of the pairs in the player-versus-player condition. The results showed that mean HR was elevated by the presence of a human opponent compared with a computer opponent, and an increase in mean HR was also observed in specific game situations (beginning of the match, toward the end of a game or match). These results suggest that the sympathetic nervous system in esports players is activated by competitive play and is modulated by the game situation. In addition, the temporal HR patterns in the opponent pairs were synchronized, suggesting that autonomic nervous system activity is synchronized in player dyads via interpersonal interaction during competitive play. Our results provide insight regarding the relationship between physiological state and psychological skill in esports professionals during esports competitions.